A cardiopulmonary study of lisdexamfetamine in adults with attention-deficit/hyperactivity disorder. (1st May 2013) - Hammerness, Paul; Zusman, Randall; Systrom, David; Surman, Craig; Baggish, Aaron; Schillinger, Mary; Shelley-Abrahamson, Rachel; Wilens, Timothy E.
Abstract: Objectives. Due to concerns about the safety of stimulants for ADHD, novel assessments of the cardiopulmonary impact of these agents are needed. Methods. An open design of lisdexamfetamine (LDX) in 15 adults with DSM-IV ADHD. Following a psychiatric evaluation and medical history, subjects underwent echocardiography (TTE) and cardiopulmonary exercise testing (CPET). LDX was titrated to 70 mg daily over 6 weeks, followed by monthly visits to 6 months. Change in TTE and CPET measures were examined following up to 6 months of LDX. Results. At endpoint, there were no significant alterations in indices of cardiac systolic performance, or in metabolic and ventilatory variables at maximum exertion ( P values >0.05). We found significant mean changes in resting LV systolic dimension and Doppler diastolic indices. Change in heart rate recovery at 1 min met statistical significance ( P = 0.05). Conclusions. We did not detect clinically meaningful changes in cardiac structure and function or in metabolic and ventilatory variables at maximum exertion in ADHD adults receiving open LDX. The clinical significance of changes in resting LV dimension and indices of diastolic function are not in the direction of cardiomyopathy. Future large sample controlled study can examine these findings, as well as stimulants' impact on heart rate recovery.